Chemorheological Studies of the Effect of Heparin on the Course of Coagulation - Overholser, K. A; Baysinger, C. B; Harris, T. R; Deveau, T (Thrombosis and Haemostasis, 1976)
The influence of sodium heparin on viscoelastic change during coagulation was determined in vitro for whole blood samples from ten normal subjects at heparin concentrations ranging from 0 to 1.45 units/(ml whole blood). A four-parameter chemorheological model was used to describe the time course of coagulation as measured by the Weissenberg Rheogoniometer. One parameter compares closely with the whole blood activated partial thromboplastin time, while the other three may be related to the chemical kinetics of clotting.The chemorheological model and experimental techniques were then tested in a dog preparation. It was found that rheological measurements are more self-consistent than either thrombelastography or the activated partial thromboplastin time for the assay of in vivo heparin in two dogs.